A common gate LNA with negative resistance for noise reduction. (December 2018) - Shokrekhodaei, Maryamsadat; Safarian, Aminghasem; Atarodi, S. Mojtaba
Abstract: This paper presents a common-gate (CG) low-noise amplifier (LNA) using a novel negative resistance to improve its noise figure (NF). The new negative-resistance CG-LNA (NR CG-LNA) shows superior performance over the conventional CG-LNAs in terms of power consumption, gain and NF. A prototype designed in 180 nm CMOS technology, occupied a silicon area of 0.57 mm 2 . The post layout simulations show a maximum gain of 20.2 dB, and a minimum NF of 2.3 dB with 8.5-mW of power consumption operating in 1.95 GHz–2.3 GHz bandwidth, which could be used in Wideband Code- Division Multiple Access (WCDMA) applications.